Microsatellite markers for Bokermannohyla species (Anura, Hylidae) from the Brazilian Cerrado and Atlantic Forest domains - Nali, Renato C. [UNESP]; Zamudio, Kelly R.; Prado, Cynthia P. A. [UNESP] (Brill Academic Publishers, 2014)
We characterized 22 polymorphic microsatellite markers for the Brazilian treefrog Bokermannohyla ibitiguara and tested their cross-amplification in B. alvarengai, B. circumdata and B. hylax. Our focal species occurs in protected and disturbed Brazilian Cerrado landscapes, a highly threatened savanna in central Brazil. Fourteen markers successfully cross-amplified for at least one congener. These microsatellites will be useful for studies of mating systems, relatedness and landscape genetics of Cerrado populations under various deforestation levels. Moreover, variable markers for B. circumdata and B. hylax will also be useful for landscape genetic studies of taxa typical of the threatened Atlantic Forest domain.
Keywords: conservation; cross-amplification; Illumina MiSeq; marker identification; Neotropical frog; next-generation sequencing